2023
DOI: 10.3389/fpls.2023.1005023
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and transcriptome analysis of the response mechanism of Solidago canadensis to the nitrogen addition environment

Abstract: Solidago canadensis is an invasive plant that can adapt to variable environmental conditions. To explore the molecular mechanism of the response to nitrogen (N) addition conditions in S. canadensis, physiology and transcriptome analysis were performed with samples that cultured by natural and three N level conditions. Comparative analysis detected many differentially expressed genes (DEGs), including the function of plant growth and development, photosynthesis, antioxidant, sugar metabolism and secondary metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…In this study, we also found that nitrogen addition significantly increased the Anth of O. articulata, indicating that this alien species could synthesize a large amount of anthocyanins in an N-enriched environment to increase its environmental tolerance, thereby effectively responding to the interspecific competition caused by A. philoxeroides invasion (Zhang et al, 2017). In addition, nitrogen addition caused a significant trade-off between the Flav and Anth of O. articulata, indicating that soil nitrogen enrichment can enhance the physiological plasticity of alien plants and thus increase their competitiveness (Wu et al, 2023). However, nitrogen addition did not have a significant effect on the Flav and Anth of A. philoxeroides in our study, which might be due to its high internal ecostoichiometric stability (Sun et al, 2019), and this may help A. philoxeroides rapidly evolve suitable growth strategies in environments with different nutrient levels (Geng et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we also found that nitrogen addition significantly increased the Anth of O. articulata, indicating that this alien species could synthesize a large amount of anthocyanins in an N-enriched environment to increase its environmental tolerance, thereby effectively responding to the interspecific competition caused by A. philoxeroides invasion (Zhang et al, 2017). In addition, nitrogen addition caused a significant trade-off between the Flav and Anth of O. articulata, indicating that soil nitrogen enrichment can enhance the physiological plasticity of alien plants and thus increase their competitiveness (Wu et al, 2023). However, nitrogen addition did not have a significant effect on the Flav and Anth of A. philoxeroides in our study, which might be due to its high internal ecostoichiometric stability (Sun et al, 2019), and this may help A. philoxeroides rapidly evolve suitable growth strategies in environments with different nutrient levels (Geng et al, 2023).…”
Section: Discussionmentioning
confidence: 95%